1993
DOI: 10.1093/ajcn/57.6.845
|View full text |Cite
|
Sign up to set email alerts
|

Detection of small changes in body composition by dual-energy x-ray absorptiometry

Abstract: The ability of dual-energy x-ray absorptiometry (DEXA) to detect small changes in body composition was studied in 17 men and women during a dehydration-rehydration protocol. Scale weight (BW) and total mass (TM) from DEXA were highly related (r > 0.99) as were estimates of fat-free mass (r = 0.99) and percent fat (r = 0.97) from DEXA and densitometry. Changes in BW of approximately 1.5 kg due to fluid loss and gain were highly correlated (r = 0.90) with both changes in TM and soft-tissue mass (STM) by DEXA but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
0
4

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(107 citation statements)
references
References 18 publications
7
96
0
4
Order By: Relevance
“…DXA compares well with other more complicated techniques, particularly in lean subjects. Previous studies have shown that DXA detects small changes in weight and resolves the changes in lean and fat components (Going et al, 1993;Tjellesen et al, 1997). However, DXA software is based on the assumption that hydration of FFM remains constant.…”
Section: Discussionmentioning
confidence: 99%
“…DXA compares well with other more complicated techniques, particularly in lean subjects. Previous studies have shown that DXA detects small changes in weight and resolves the changes in lean and fat components (Going et al, 1993;Tjellesen et al, 1997). However, DXA software is based on the assumption that hydration of FFM remains constant.…”
Section: Discussionmentioning
confidence: 99%
“…The height, weight and waist circumference were measured with the subjects wearing a light gown, but no shoes. Body composition was measured using dual energy X-ray absorptiometry (Lunar Prodigy; GE Medical Systems, Waukesha, WI, USA), which is a sensitive test to quantify changes in lean and fat mass in vivo (Going, 1993) and assessing regional fat distribution (Taylor et al, 1998). All of the scans were analyzed with Lunar software, package l.35.…”
Section: Methodsmentioning
confidence: 99%
“…However, the results were similar if BMD was used as the dependent variable in these models. In addition, lean mass measurements by DXA can be affected by the state of hydration [62]. Overestimation of muscle mass in the paretic leg may occur since swelling in the paretic arm is quite common in individuals with stroke [63].…”
Section: Limitationsmentioning
confidence: 99%